The influence of economic incentives and regulatory factors on the adoption of treatment technologies - Bech, Mickael (2009)
The Technological Change in Health Care Research Network collected unique patient-level data on three procedures for treatment of heart attack patients (catheterization, coronary artery bypass grafts and percutaneous transluminal coronary angioplasty) for 17 countries over a 15-year period to examine the impact of economic and institutional factors on technology adoption. Specific institutional factors are shown to be important to the uptake of these technologies. Health-care systems characterized as public contract systems and reimbursement systems have higher adoption rates than public-integrated health-care systems. Central control of funding of investments is negatively associated with adoption rates and the impact is of the same magnitude as the overall health-care system classification. GDP per capita also has a strong role in initial adoption. The impact of income and institutional characteristics on the utilization rates of the three procedures diminishes over time.